Free-form surface-oriented five-axis single-point color printing technology. (October 2019) - Shen, Hongyao; Liu, Senxin; Wu, Senyang; Zhang, Linchu; Sha, Jianfeng
Two-dimensional inkjet technology has made great progress in colorful plane printing. However, color printing technology for three-dimensional model is currently only at the exploratory stage; there are few reports on this issue. In this article, a free-form surface-oriented five-axis single-point printing technology with exclusive color nozzle is proposed. The single-point color nozzle consists of four print heads: prints cyan, magenta, yellow, and black pigment. For high-efficiency color printing, each print head prints on the same single point when the color nozzle moves along the surface. The method of color printing along the surface normal direction is proposed as normal direction printing mode. The algorithm of print point generation is introduced, and the path planning method of self-adaptive slicing and self-adaptive printing filling is proposed. In addition, a five-axis single-point printing platform is designed. Experiments are done to demonstrate the feasibility of the printing system.